2016
DOI: 10.1021/acs.est.6b00183
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Accumulation of Polystyrene Microplastics in Zebrafish (Danio rerio) and Toxic Effects in Liver

Abstract: Microplastics have become emerging contaminants, causing widespread concern about their potential toxic effects. In this study, the uptake and tissue accumulation of polystyrene microplastics (PS-MPs) in zebrafish were detected, and the toxic effects in liver were investigated. The results showed that after 7 days of exposure, 5 μm diameter MPs accumulated in fish gills, liver, and gut, while 20 μm diameter MPs accumulated only in fish gills and gut. Histopathological analysis showed that both 5 μm and 70 nm P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
586
7
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,569 publications
(689 citation statements)
references
References 45 publications
(80 reference statements)
31
586
7
9
Order By: Relevance
“…Even the consumption of oysters which rather high accumulation of microplastics (Galloway and Lewis, 2016) would hardly approach the amounts used in the experiments. How do microplastics elicit the adverse effects seen in mouse liver and the zebrafish liver in the earlier report (Lu et al, 2016)? To reach the liver, the ingested microplastics would need to somehow negotiate the gut-vascular barrier (Spadoni et al, 2015) or be taken up by intestinal enterocytes and transported across the epithelial mucosal lining in a manner akin to transcytosis of macromolecules.…”
Section: Implications and Perspectivesmentioning
confidence: 97%
See 2 more Smart Citations
“…Even the consumption of oysters which rather high accumulation of microplastics (Galloway and Lewis, 2016) would hardly approach the amounts used in the experiments. How do microplastics elicit the adverse effects seen in mouse liver and the zebrafish liver in the earlier report (Lu et al, 2016)? To reach the liver, the ingested microplastics would need to somehow negotiate the gut-vascular barrier (Spadoni et al, 2015) or be taken up by intestinal enterocytes and transported across the epithelial mucosal lining in a manner akin to transcytosis of macromolecules.…”
Section: Implications and Perspectivesmentioning
confidence: 97%
“…Microplastics are taken up and could accumulate in the gills and gut tissues of mussels and oysters (von Moos et al, 2012;Van Cauwenberghe et al, 2015;Paul-Pont et al, 2016;Sussarellu et al, 2016), with histopathology and stress responses documented with the former and reproductive deficiencies noted for the latter, as well as other marine invertebrates (Wright et al, 2013). More recent work has also documented adverse effects of microplastic ingestion in aquatic vertebrates such as the zebrafish (Lu et al, 2016;Chen et al, 2017). Ren's laboratory, for example, reported that 5 and 20 µm polystyrene micro-particles accumulate in gills, gut tissues and in the liver of zebrafish (Lu et al, 2016).…”
Section: A Commentary Onmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been found that such exposure to nanoparticles can change fish metabolism (Cedervall et al, 2012). Plastic exposure has also been found to change gene expression for example up-regulation of fatty acids and down regulation of amino acids (Lu et al, 2016) while also other impacts following microplastic exposure have been found, such as hepatic stress .…”
Section: Effects Of Ingestion On Fish and Invertebrates From Laboratomentioning
confidence: 99%
“…A Baía de Guanabara, apesar de ser considerado um dos ambientes costeiros mais degradados do país, devido ao seu alto grau de eutrofização antrópica (Coelho, 2007;Soares-Gomes et al, 2016) Alguns pesquisadores já relataram que organismos de diferentes tamanhos estão sendo afetados pela contaminação com microplásticos (Thompson, R. C. et al, 2004;Hidalgo-Ruz et al, 2012;Lu et al, 2016).…”
Section: Preocupação Com a Biotaunclassified